2002
DOI: 10.1021/jf020448e
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the Ionotropic GABA Receptor Response by Whiskey Fragrance

Abstract: It is well-known that the target of most mood-defining compounds is an ionotropic gamma-aminobutyric acid receptor (GABA(A) receptor). The potentiation of the response of these inhibitory neurotransmitter receptors induces anxiolytic, sedative, and anesthetic activity in the human brain. To study the effects of whiskey fragrance on the GABA(A) receptor-mediated response, GABA(A) receptors were expressed in Xenopus oocyte by injecting rat whole brain mRNA or cRNA prepared from the cloned cDNA for the alpha(1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 36 publications
3
42
0
Order By: Relevance
“…We have reported in previous papers [8][9][10]19,20) that the fragrant compounds in essential oils, perfumes, tea, coffee and whiskey potentiated the response of the GABA A receptors, and proposed that they might have contributed in part to altering moods and relaxing consciousness through their direct potentiation of the receptors, since it is known that potentiation of the GABA A receptor response by various drugs induces anxiolytic, anticonvulsant and sedative activity. 3) We further found that the fragrant compounds in whiskey played an important role in the potentiation of the GABA A receptor response and possibly in the sedative effect of whiskey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported in previous papers [8][9][10]19,20) that the fragrant compounds in essential oils, perfumes, tea, coffee and whiskey potentiated the response of the GABA A receptors, and proposed that they might have contributed in part to altering moods and relaxing consciousness through their direct potentiation of the receptors, since it is known that potentiation of the GABA A receptor response by various drugs induces anxiolytic, anticonvulsant and sedative activity. 3) We further found that the fragrant compounds in whiskey played an important role in the potentiation of the GABA A receptor response and possibly in the sedative effect of whiskey.…”
Section: Discussionmentioning
confidence: 99%
“…6) These structurally diverse compounds enhance the response of GABA A receptors in the presence of a low concentration of GABA. We have reported in previous papers the inhibition or potentiation of the response of GABA A receptors by the various components present in foods, 7) beverages 8,9) and essential oils used for aromatherapy, 10) and thereby found that the fragrant compounds generally potentiated the GABA A receptor responses. We also proposed a simple kinetic model for the potentiation of GABA A receptor responses.…”
mentioning
confidence: 96%
“…Yamada et al (1994) found that inhaling lavender oil vapor blocked pentetrazole-induced convulsions in mice, suggesting a potentiation of the GABA A receptor's response by lavender oil. The intraperitoneal administration of ethyl phenylpropanoate, which is one of the fragrances in whiskey and potentiates the response of GABA A receptors, delayed significantly convulsions caused by pentetrazole in mice, suggesting that ethyl phenylpropanoate potentiates the response of GABA A receptors against inhibition of the response by pentetrazole (Hossain et al, 2002a).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Though fragrant components are much less numerous than ethanol in whiskey, the dosepotentiation relationship showed that they potentiated the response of GABA A receptors a thousand times more than ethanol (Fig. 8) (Hossain et al, 2002a). The potentiation of the GABA A receptor's response by whiskey can be measured by adding whiskey itself to the GABA solution, since whiskey is a distilled liquor and contained no GABA but various compounds are moved into whiskey from an oak barrel during aging.…”
Section: Potentiation Of the Response Of Gaba A Receptors By Liquorsmentioning
confidence: 99%
“…The potentiation of the response of these receptors by drugs such as benzodiazepine, pentobarbital and anesthetics induces tranquilizing, sleepinducing or anesthetic responses in humans (Nicholls, 1994;Chebib & Johnston, 2000;Harrison et al, 2000). It was found that fragrant compounds such as terpinen-4-ol, 1-octen-3-ol, and linalool potentiated the response of GABA A receptors expressed in Xenopus oocytes after injection of the receptor poly(A) + RNA or cRNA (Aoshima & Hamamoto, 1999;Aoshima et al, 2001;Aoshima et al, 2006;Hossain et al, 2002aHossain et al, , 2004Hossain et al, , 2007Hossain et al, 2002b). Initially, GABA A receptors expressed in Xenopus oocytes injected with rat whole brain mRNA were used for measurements, but fragrances had similar effects on receptor response to that obtained on injecting cRNA of the α 1 and β 1 subunits of bovine GABA A receptors (Aoshima et al, 2001).…”
mentioning
confidence: 99%